Assessing Children's Anxiety Using the Modified Short State-Trait Anxiety Inventory and Talking Mats: A Pilot Study - Stefan Nilsson; Margret Buchholz; Gunilla Thunberg (Nursing Research and Practice)
Background. Preoperative anxiety complicates treatment and requires assessment by nurses in children. Children, with or without disability, are helped when pictures are used to support communication. The purpose of this pilot study was to test the reliability and validity of the modified short State-Trait Anxiety Inventory (STAI) using a modified Talking Mats method in children undergoing day surgeries. Method. A modified short STAI with pictorial support along the lines of the Talking Mats method was pre- and postoperatively administered to 42 typically developing children aged three to nine years. The parents assessed the children’s anxiety, simultaneously and independently, by scoring the short STAI by proxy. Results. The modified short STAI showed moderate internal consistency and good construct validity in the age group seven to nine years. Conclusions. The results of this study support the use of the instrument for self-reports in children aged seven to nine years. Future research will explore the possibilities of also using this instrument for children with cognitive and communicative difficulties.